2012
DOI: 10.1021/ic3007662
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties and Behaviors of Cuprous Oxide Cubes under High Pressure

Abstract: An accurate in situ electrical resistivity measurement of cuprous oxide cubes has been conducted in a diamond anvil cell at room temperature with pressures up to 25 GPa. The abnormal electrical resistivity variation found at 0.7-2.2 GPa is attributed to the phase transformation from a cubic to a tetragonal structure. Three other discontinuous changes in the electrical resistivity are observed around 8.5, 10.3, and 21.6 GPa, corresponding to the phase transitions from tetragonal to pseudocubic to hexagonal to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Hence we infer that the phase transition of VO 2 have a big possibility to be reversible. 29,30 However, in situ XRD experiments should be done to give direct evidence in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Hence we infer that the phase transition of VO 2 have a big possibility to be reversible. 29,30 However, in situ XRD experiments should be done to give direct evidence in the future.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the pressure-induced disruption of cubes can produce abundant boundaries and microstrains in the sample, adding additional energy levels into the band gap and increasing the concentration of free charge carriers. 27,32 The inverse trend of the relaxation frequency of the grain and grain boundaries with pressure indicates a negative correlation between the relaxation time and pressure.…”
Section: High-pressure Ac Impedance Spectrum Analysismentioning
confidence: 99%
“…Generally, the structure transitions of a material can affect its electrical properties. [17] At ambient conditions and high pressure, the pressure-induced phase transitions have been well studied before. The results indicated that there is no sign of phase transitions at 8 GPa and the C 60 cages collapse and form an amorphous phase of carbon at 16-20 GPa.…”
Section: Resultsmentioning
confidence: 99%